Health-related quality of life profiles among overweight and obese individuals in a Malaysia’s public university - Pei Lin, Lua; Nurul Afiedia Roslim, Roslim; Aryati, Ahmad; Mardiana, Mansor; Myat Moe, Thwe Aung; Farrahdilla, Hamzah (2021)
Introduction: The global epidemic of overweight and obesity presents a major challenge in the health status of the society as it impacts both physiological and psychosocial aspects of the individuals. Hence, this study attempts to explore HRQoL profile among staff and students with BMI≥25kg/m2 of a public university in Terengganu, Malaysia and to compare this profile based on their socio-demographic variables. Experimental: This cross-sectional study employed convenience sampling. Anthropometric measurement comprised height (cm), weight (kg), and body mass index (BMI), were calculated. HRQoL was measured using the Short Form 12 Health Survey (SF-12) physical component score (PCS) and mental component score (MCS), with higher scores indicated better quality of life. Data was analysed using SPSS 23.0, employing descriptive and parametric tests. Results: Eligible 107 Muslim participants were recruited (age = 26.28±8.01; female = 82.2%; students = 71.0%). Over half of the participants were obese (n=58, 54.2%). Outcomes demonstrated the participants’ HRQoL was moderate, in which overweight participants had better PCS (mean = 47.38 ± 6.99 versus 45.76 ± 9.82) but lower in MCS (mean = 40.50±8.31 versus 41.34±8.39), compared to obese individuals. Nevertheless, there were no different variables in association between the selected socio-demographic variables i.e. age of participants, gender, occupations and income levels either with PCS or MCS (p>0.05). Conclusion: These results suggest a potentially greater risk of poor HRQoL among excess weight individuals with regard to the mental health component. Thus, efforts should be escalated in weight loss approaches to continuously improve mental status of overweight and obese individuals.